Revisiting the role of education in attitudes toward immigration in different contexts in Europe - Karen Umansky; Daniela Weber; Wolfgang Lutz (Genus)
Abstract Among the individual determinants of attitudes toward immigration, the liberalising role of education is well known—those with higher levels of education tend to be more in favour of immigration. However, recent socioeconomic changes and idiosyncratic differences between European countries prompt us to reassess the role of education, given these contextual differences. Does it still apply, and is it universal? Moreover, does this relationship apply to both cultural and economic attitudes toward immigration? Using data from the European Social Survey, we analyse the role of education and socioeconomic changes in shaping economic and cultural attitudes toward immigration in 15 European countries over 16 years using a hierarchical model with cross-classified random effects. In our analysis, we distinguish between Eastern European and non-Eastern European countries. Our results indicate a robust positive and significant association between higher levels of education and more tolerant attitudes toward immigration in both aspects. However, they also reveal that the strength of this relationship varies between the two attitudes by context and region. For example, higher migrant inflow rates attenuate education’s liberalising and empowering role in shaping cultural attitudes in non-Eastern European countries but are not significant in Eastern European countries. Thus, our findings contribute to the literature examining the role of context in the established relationship between education and immigration attitudes while providing insights into regional differences.